Antibacterial susceptibility patterns of methicillin resistant staphylococcus spp. from a tertiary reference hospital. Issue 1 (2012) - Ağalar, Canan; Göçmen, Jülide Sedef; Kılıç, Dilek; Kaygusuz, Sedat; Karabıçak, Çiğdem
No abstract available